Market research in practice : how to get greater insight from your market - Hague, Paul N.; Hague, Nick, 1974-; Morgan, Carol-Ann, 1958- (London : Kogan Page, 2013)
" Lively and accessible, Market Research in Practice is a practical introduction to market research tools, approaches and issues. Offering a clear, step-by-step guide to the whole process - from planning and executing a project through to analysis and presentation of the findings, the book explains how to use tools and methods effectively and obtain the most reliable results. With new chapters on using market research, international aspects and new research trends (including coverage of social media research and mobile surveys) this fully updated second edition also includes the latest information on carrying out market research design, secondary research, sampling and statistics, questionnaire design, data analysis and reporting.Accompanied by a range of online tools and templates and supported throughout by examples from real market research practice, this is a valuable guide for students, researchers, marketers and users of market research"--
Machine generated contents note: Preface01 Introduction -- Who needs market research? -- New roles for market research -- The effect of regional culture on the use of market research -- The use of market research in business models and frameworks -- Consumer and business-to-business market research -- The scope of market research information -- Quantitative and qualitative research -- The market research process -- The organization of market research -- Summary02 Uses of market research -- Understanding markets -- Understanding customers -- Understanding and developing the offer -- Positioning the brand and communications -- Summary03 Market research design -- What is worth researching? -- Market research suppliers -- The market research brief: a statement of the problem/opportunity -- The market research proposal: the return of brief (ROB) -- The information required -- The accuracy -- The budget -- The timetable -- What to expect in a proposal (return of brief) -- Summary04 Desk research -- A veritable gold mine -- An important principle of desk research -- Sources of sources: the high-level view -- Industry experts -- The internet -- Online market reports -- The press -- Company data -- Government statistics -- Trade and industry bodies -- Directories and lists -- The range of information available from desk research -- Planning, recording and evaluating desk research -- The limits of desk research -- Summary05 Focus groups -- The focus group -- The people that make up a focus group -- When to use focus groups -- Areas of special consideration -- Planning and recruiting groups -- Number of groups -- Venues of groups -- Getting participants to attend -- The group moderator -- Tools of the group moderator -- Summary06 Depth interviewing -- Why use depth interviews? -- Depth interviews in market research design -- How many depth interviews are needed? -- The role of the telephone in depth interviewing -- Winning cooperation for the interview -- The principles of interviewing -- The interview itself -- The line of questioning -- Developing the discussion guide for the interview -- Probes and prompts -- Summary07 Observation and ethnography -- Observation: a research method you can believe -- When to use observation -- The audit: a major application for observation -- Observation in shopping surveys -- Observation in product research -- Observation in poster checks -- Observation in checking television viewing -- Setting up observation programmes -- Reporting observational data -- Summary08 Sampling and statistics -- The principles of sampling -- Random sampling in consumer markets -- Choosing the size of the sample -- Sampling error -- Random sampling and non-response -- Quota samples -- Sampling in business-to-business markets -- Using statistics to derive importance of factors -- Using statistics to arrive at needs-based segmentations -- Summary09 Questionnaire design -- What is so difficult about designing a questionnaire? -- The role of questionnaires -- Different types of questionnaires -- Different types of questions -- Behavioural questions -- Attitudinal questions -- Classification questions -- Three steps in questionnaire design -- Formulating the questions -- Arranging the questionnaire layout -- Piloting and testing the draft questionnaire -- Special questionnaires: conjoint analysis -- Trade-off grids (SIMALTO -- simulated multi-attribute level trade-off) -- Summary10 Self-completion questionnaires -- The ubiquitous self-completion questionnaire -- When to use and when not to use self-completion questionnaires -- Principles of designing self-completion questionnaires -- Good practice in self-completion questionnaires -- Summary11 Face-to-face interviewing -- Advantages of face-to-face interviews -- Disadvantages of face-to-face interviews -- Street interviews -- Household interviews -- Questionnaire design -- Response rates to surveys: an industry problem -- Hall tests (mall intercepts) -- Summary12 Telephone interviewing -- Why interview by telephone? -- CATI: computer-assisted telephone interviewing -- The art of telephone interviewing: carrying out a successful interview -- Limitations of telephone interviews -- Summary13 Online surveys -- The life cycles of research methods -- Sending out e-surveys -- The growth of online panels -- The advantages and disadvantages of panel research -- Organizing an online survey -- Online focus groups -- Collecting information from a website -- Google and the rise of the DIY researcher -- Mobile surveys -- Using the net to pose questions -- Summary14 Data analysis -- The analysis of closed questions -- Data analysis of open-ended questions -- Analysis of numerical responses -- A note on data validation -- Multivariate analysis -- Qualitative data analysis -- Semiotics and qualitative research -- Summary15 Reporting -- Common rules for both written reports and presentations -- Reporting qualitative data -- Reporting quantitative data -- Drawing conclusions -- Making a presentation -- Summary16 International market research -- Seeing things more clearly -- The structure of the global market research industry -- Response rates internationally -- Measuring attitudes across nations -- Coordinating multi-country studies -- Using desk research (secondary research) to carry out international market research -- Summary17 Research trends -- Drivers of change -- Trends in quantitative research -- Trends in qualitative research -- Making questionnaires more engaging -- Trends amongst users of market research -- Specialization in market research skills -- SummaryBibliography -- Index.nues of groups -- Getting participants to attend -- The group moderator -- Tools of the group moderator -- Summary06 Depth interviewing -- Why use depth interviews? -- Depth interviews in market research design -- How many depth interviews are needed? -- The role of the telephone in depth interviewing -- Winning cooperation for the interview -- The principles of interviewing -- The interview itself -- The line of questioning -- Developing the discussion guide for the interview -- Probes and prompts -- Summary07 Observation and ethnography -- Observation: a research method you can believe -- When to use observation -- The audit: a major application for observation -- Observation in shopping surveys -- Observation in product research -- Observation in poster checks -- Observation in checking television viewing -- Setting up observation programmes -- Reporting observational data -- Summary08 Sampling and statistics -- The principles of sampling -- Random sampling in consumer markets -- Choosing the size of the sample -- Sampling error -- Random sampling and non-response -- Quota samples -- Sampling in business-to-business markets -- Using statistics to derive importance of factors -- Using statistics to arrive at needs-based segmentations -- Summary09 Questionnaire design -- What is so difficult about designing a questionnaire? -- The role of questionnaires -- Different types of questionnaires -- Different types of questions -- Behavioural questions -- Attitudinal questions -- Classification questions -- Three steps in questionnaire design -- Formulating the questions -- Arranging the questionnaire layout -- Piloting and testing the draft questionnaire -- Special questionnaires: conjoint analysis -- Trade-off grids (SIMALTO -- simulated multi-attribute level trade-off) -- Summary10 Self-completion questionnaires -- The ubiquitous self-completion questionnaire -- When to use and when not to use self-completion questionnaires -- Principles of designing self-completion questionnaires -- Good practice in self-completion questionnaires -- Summary11 Face-to-face interviewing -- Advantages of face-to-face interviews -- Disadvantages of face-to-face interviews -- Street interviews -- Household interviews -- Questionnaire design -- Response rates to surveys: an industry problem -- Hall tests (mall intercepts) -- Summary12 Telephone
"First published in Great Britian and the United States in 2004."--T.p. verso.
Includes bibliographical references (pages 234-249) and index.
Keywords: Marketing research; BUSINESS & ECONOMICS / Marketing / Research; BUSINESS & ECONOMICS / Marketing / General; Marketing research